'A Man of Violent and Ungovernable Temper': Can Fiction Fill Silences in the Archives?. Issue 1 (2nd January 2021) - Collins, Katherine E
ABSTRACT: Biofiction can be defined as fiction about a named, real person and is characterised by creativity, invention, and imaginative exploration. In this essay I deploy a mixture of nonlinear narrative and theoretical writing to explore the argument that creative ways of responding to archival silences illuminate, and also complicate, our attempts to recover women's lives from obscurity. As the text evolves, the narrative sections become more invented, more experimental, something more like fiction.